Origins of the divergent evolution of mountain glaciers during deglaciation: Hofsdalur cirques, Northern Iceland. (1st December 2021) - Tanarro, Luis M.; Palacios, David; Fernández-Fernández, José M.; Andrés, Nuria; Oliva, Marc; Rodríguez-Mena, Manuel; Schimmelpfennig, Irene; Brynjólfsson, Skafti; Sæmundsson, þorsteinn; Zamorano, José J.; Úbeda, Jose; ,; et al.
Abstract: The aim of this work is to study the process of transformation of debris-free mountain glaciers into debris-covered glaciers and rock glaciers, and to examine the factors driving diverging evolution in similar glacial systems. The study area is the Hofsdalur valley, in the Tröllaskagi peninsula (northern Iceland), where several cirques host a great diversity of glaciers and rock glaciers as well as various glacial landforms. Four adjacent cirques have been analysed through a multidisciplinary approach: geomorphological analysis, boulder surface displacement tracking, quantification of recent glacier changes, three dimensional palaeoglacier reconstruction, equilibrium-line altitude calculations and relative and direct dating methods applied to surface boulders. Dating methods included in situ 36 Cl cosmic-ray exposure dating, Schmidt hammer weathering measurements and lichenometric dating. The results confirm that glaciers in Hofsdalur followed an evolution pattern similar to that observed in other cirques in the Tröllaskagi peninsula. During the Younger Dryas (12.9–11.7 ka) many of those cirques hosted debris-free glaciers, whose retreat started in the early Holocene. Distinct retreat dynamics and cirque floor elevation conditioned the subsequent glacial evolution. In some Tröllaskagi cirques, the ice completely covered the headwalls, which consequently did not supply debris onto the glacier surface, which remained debris-free. In most of these cirques, however, glacier retreat enhanced paraglacial processes and the ice-free cirque walls generated a high debris supply onto the glacier surface. As a result, the glaciers evolved towards debris-covered glaciers or rock glaciers, depending on the local topographical setting. In the lower cirques they collapsed immediately after their formation. At higher altitudes, above the lower permafrost limit, these ice-cored landforms have survived until the present day, but they have been stagnant since the Holocene Thermal Maximum, while the heads of these cirques have hosted debris-free glaciers during the Late Holocene. Highlights: A multi-proxy approach is used to establish the evolution of Tröllaskagi cirque glaciers. The four cirques hosted debris-free glaciers during the Younger Dryas. Glaciers evolved to different forms depending on paraglacial processes. Debris-covered glaciers and rock glaciers became stagnant during Middle Holocene. The upper sectors of the glaciers reformed as debris-free glaciers in Late Holocene.